2015
DOI: 10.1039/c4an02283a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selenium in serum in the presence of gadolinium with ICP-QQQ-MS

Abstract: Gadolinium (Gd)-based magnetic resonance imaging (MRI) contrasting agents interfere with the determination of selenium (Se) when analysed by single quadrupole inductively coupled plasma-mass spectrometry (ICP-MS). This paper demonstrates that an ICP-triple quadrupole-MS (ICP-QQQ-MS) with oxygen mass shift overcomes Gd(++) interference on Se(+) and mitigates typically encountered matrix and spectral based interferences. Normal human serum was diluted in a solution containing isopropanol, EDTA, NH4OH and Triton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Unfortunately, only a small number of target ions can react with O 2 . Lower sensitivities of the analytes were therefore observed . Since a pure collision was employed in the He mode, the kinetic energy loss of target ions would occur inevitably during this process .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, only a small number of target ions can react with O 2 . Lower sensitivities of the analytes were therefore observed . Since a pure collision was employed in the He mode, the kinetic energy loss of target ions would occur inevitably during this process .…”
Section: Resultsmentioning
confidence: 99%
“…The very first publications in this research field dealt with the determination of S and P in organic matrices [13,14], whereby S + and P + ions were converted into their corresponding hindered by spectral overlap with Ar-based interfering ions, but also with doubly charged ions from the rare earth elements. Jackson et al [31] and Bishop et al [32] showed that O-atom transfer can also be a useful approach in this context. Bolea-Fernandez et al [33] evaluated the performance of different cell gases and conditions (e.g., use of the instrument in "vented mode", use of He as a collision gas and use of O2 and CH3F as reaction gases) for Se determination and came to the conclusion that O2 does not seem to be the preferred reaction gas, which may be due to a reduced signal stability and a low reaction efficiency of Se with O2.…”
Section: O-atom Transfermentioning
confidence: 99%
“…It may therefore be assumed that in the upcoming years, ICP-MS/MS will be increasingly used, as it provides an elegant response to the shortcomings of single-quadrupole ICP-MS (and maybe even sector-field ICP-MS in some cases) for several applications, where (ultra)trace elements have to be determined in complex matrices. [41] As, Au, B, Be, Br, Cl, I, P, Se O2 charge transfer: X + + O2 ---> O2 + + X fundamental study [13] P (31) O2 mass shift: P + --> PO + determination of P and S in proteins S (32,34) mass shift: S + --> SO + [26] B…”
Section: Ch3fmentioning
confidence: 99%
“…Another mechanism by which gadolinium can interfere with elemental analysis by ICP-MS is by double charge interference. 7,10,11 For example, 156 Gd can interfere with selenium analysis if a clinical laboratory chooses 78 Se as the ideal isotope to analyse. Theoretically, most inductively coupled plasma assays remove one electron from the outer shell of the atom resulting in a + 1 charge.…”
Section: Introductionmentioning
confidence: 99%